МОНГОЛЧУУДЫН УЛС ТӨРИЙН СОЁЛД НӨЛӨӨЛЖ БУЙ НИЙГЭМ, ЭДИЙН ЗАСГИЙН ХҮЧИН ЗҮЙЛС - Ж.ТӨРТОГТОХ; Д.Хулан (Politology, 2023)
Political culture refers to the level of political culture maturity and the attitudes and behavior of the common people who make up the society. As a society makes a systemic political transition, the political culture also changes and develops depending on the values and ideals of the system that it aims to develop. Although Mongolians are facing 32nd anniversary of the transition to democracy to socialism, it is still in the list of distorted democracy by researchers and international organizations. Thus, it is explored that how the social and economic change in the Mongolian society is influencing the maturity of political culture and democratic system. In the other words, a problem is concluded by performing a correlation analysis between social and economic factors to clarify how the current political development and advancement is influenced by the conventional political culture and thinking, as well as the factors of the transition period.